Impact of diamond tool wear on the surface finish of lithium silicate glass ceramics machined with the assistance of CAD/CAM systems - Simba, Bruno Galvão [UNESP]; Alves, Manuel Fellipe Rodrigues Pais; Villela, Tales Ferreira; Ribeiro, Marcos Valério [UNESP]; Strecker, Kurt; dos Santos, Claudinei (Springer Nature, 2023)
In this work, the effect of wear of diamond tools on the surface roughness and its influence on the mechanical properties of dental lithium silicate glass–ceramic milled by a CAD/CAM system was investigated. Cutting tools with distinct tool life, new cutting tool (NCT), mid-life cutting tool (MLCT) corresponding to cumulative 2 h of milling and end-of-life cutting tool (ELCT) corresponding to cumulative 4 h of milling were used for machining commercial lithium metasilicate LM, Li2SiO3, using a Sirona inLab MC X5® milling machine. The different tools were characterized by scanning electron microscopy (SEM). Their microstructure indicated a depletion of diamond particles on the surface, as a function of the accumulated time of use. The lithium metasilicate samples were characterized by their phase composition using X-ray diffraction (XRD) analysis and their microstructure by (SEM). Furthermore, the mechanical properties Vickers hardness, fracture toughness and the elastic parameters were determined. The as-received LM samples presented 44% of Li2SiO3 and 56% amorphous phase. These LM samples exhibited a Vickers hardness of 6.1 ± 0.3 GPa, a fracture toughness of 1.3 ± 0.2 MPa m1/2, a modulus of elasticity of 82.3 GPa and a Poisson’s ratio of 0.16. The surface roughness of the machined LM samples was evaluated using a roughness meter. The profilometry measurements of the machined LM samples indicate a slight increase in the roughness parameter Ra with increasing wear of the cutting tools, i.e., using NCT, MLCT or ELCT tools, in addition to a considerable increase in the total height of the Rt profile from 11 to 17 µm. The formation of small microcracks during machining may nucleate new flaws in the material, if the critical initial crack size is exceeded. Aspects related to the performance of heat treatments for crystallization of lithium disilicate, Li2Si2O5, and its implications on the microstructure, softening of the residual amorphous phase and its surface roughness are discussed.
Keywords: CAD/CAM milling; Dental glass–ceramics; Mechanical properties; Roughness